(untitled) (Devenires, 2006)
In the present translation of Heidegger’s aphorisms we have tried to eliminate the imprecisions of previous translations (without disqualifying them), and propose to show that Heidegger is one alone: poet and philosopher, which concentrate their efforts to find the meaning of Being. We consider that Heidegger pointed out the closeness and the required dialog between poet and thinker, not without observing the distance between them: “the naming of the poet and the saying of the thinker have —for Heidegger— the same origin, both coincide in a faint and, at the same time, clear difference”.